REPRODUCTIVE PERFORMANCE OF BALI CATTLE IN BREEDING INSTALATION BALI CATTLE OF SOBANGAN - Saputra, I Gede Hendi; Trilaksana, I Gusti Ngurah Bagus; Puja, I Ketut (Buletin Veteriner Udayana, 2022)
This study was conducted to investigate the reproductive performance of bali cattle in breeding instalation bali cattle of Sobangan, Badung, Bali. Totaling 288 heifers were use to represents the benchmark reproductive performance of bali cattle. Data collected were service per conception (S/C), gestation length, birth weight, and   postpartum estrus . The overall means for service per conception (S/C), gestation length, birth weight, and   postpartum estrus were 1,3 times;  284,63±10,73 kg; 17,89±1,04 kg; dan 101,71±32,31 days.